Role of mannitol metabolism in the pathogenicity of the necrotrophic fungus Alternaria brassicicola - Calmes, Benoit; Guillemette, Thomas; Teyssier, Lény; Siegler, Benjamin; Pigné, Sandrine; Landreau, Anne; Iacomi, Beatrice; Richomme, Pascal; Lemoine, Rémi; Simoneau, Philippe (Frontiers in Plant Science, 2013)
In this study, the physiological functions of fungal mannitol metabolism in the pathogenicity and protection against environmental stresses were investigated in the necrotrophic fungus Alternaria brassicicola. Mannitol metabolism was examined during infection of Brassica oleracea leaves by sequential HPLC quantification of the major soluble carbohydrates and expression analysis of genes encoding two proteins of mannitol metabolism, i.e. a mannitol dehydrogenase (AbMdh), and a mannitol-1-phosphate dehydrogenase (AbMpd). Knockout mutants deficient for AbMdh or AbMpd and a double mutant lacking both enzyme activities were constructed. Their capacity to cope with various oxidative and drought stresses and their pathogenic behaviour were evaluated. Metabolic and gene expression profiling indicated an increase in mannitol production during plant infection. Depending on the mutants, distinct pathogenic processes, such as leaf and silique colonization, sporulation, survival on seeds, were impaired by comparison to the wild-type. This pathogenic alteration could be partly explained by the differential susceptibilities of mutants to oxidative and drought stresses. These results highlight the importance of mannitol metabolism with respect to the ability of A. brassicicola to efficiently accomplish key steps of its pathogenic life cycle.